Tanks - Haskew, Michael E. (Inside out, 2019)
Tanks is a comprehensive study of the key tanks and armoured fighting vehicles built since World War I. Arranged chronologically, each vehicle has a cutaway artwork labelled with key items of interest, and photographs showing both the interior and exterior, with full design and development history and detailed specifications